Some slicing issues in rapid prototyping / Boppana Veeraiah Chowdary and Divesh R. Sahatoo - Chowdary, Boppana Veeraiah; Sahatoo, Divesh R. (UiTM Press, 2011)
Rapid prototyping (RP) processes such as fused deposition modeling (FDM) and stereo lithography (SL) are being widely used in the industry with great potential for direct digital manufacturing of functional parts. In the RP process, surface finish and build time are important and are affected due to improper selection of slice thickness. It is evident that there is a strong relation between the slicing and tessellation process for which more scientific efforts are necessary to develop methods for creating more efficient STL files. The aim of this study is to show the effect of slicing on the surface finish, layering error and build time of a prototype. Furthermore, this study shows how tolerance and slice thickness are related in creating more efficient STL files. In this regard, three objects were modeled for generation of STL files. Each object's STL file was sliced with different slice thickness values. Screenshots approach was used to show the slicing effect on layering error. The build times were calculated and documented. The study results show that slice thickness has a great impact on several factors. The results will serve the industry in understanding how the STL generation and slicing process can be carried out effectively for efficient utilization of various resources.